The development of a pilot control adaptation metric for simulation perceptual fidelity assessment - Memon, Wajih A.; Cameron, Neil; White, Mark D.; Padfield, Gareth D.; Lu, Linghai (Vertical Flight Society, 2021)
This paper reports the use of a control compensation metric to examine pilot adaptation in the objective assessment of simulation perceptual fidelity. The utility of the proposed metric to quantify different levels of pilot control compensation, hence adaptation, whilst flying low and high aggression tasks is explored. The tasks were conducted by different test pilots using the Heliflight-R simulator to examine the effect of additional transport delays on overall simulation perceptual fidelity. A weighted adaptive control compensation metric shows strong correlation with (Cooper-Harper) Handling Qualities and Simulation Fidelity Ratings awarded for each of the tasks. Moreover, in combination with a time-varying frequency-domain exposure, the metric is shown to be insightful for understanding variations in the pilots’ assessment of simulation perceptual fidelity.